Larval description and chaetotaxic analysis of Gyrinus monrosi Mouchamps, 1957 (Coleoptera: Gyrinidae) - Michat, Mariano Cruz (2010)
The three larval instars of the Neotropical gyrinid species Gyrinus (Oreogyrinus) monrosi Mouchamps, 1957 are described and illustrated for the first time including detailed morphometric and chaetotaxic analyses of the cephalic capsule, head appendages and legs. Larvae of Gyrinus Müller, 1764 are diagnosed by the following combination of characters: cephalic capsule not constricted at level of occipital region; shape of medial lobe of frontoclypeus; presence of a mandibular retinaculum; lacinia broad, indented apically; claws with basoventral spinulae. On the other hand, larvae of the subgenus Oreogyrinus Ochs, 1935 have the medial hooks of the abdominal segment X slightly longer than the lateral hooks, whereas in the subgenus Neogyrinus Hatch, 1925 the medial hooks are much shorter than the lateral hooks. Regarding chaetotaxy, Gyrinus differs from Andogyrus Ochs, 1924 and Dineutus Macleay, 1828 in the absence of additional setae on the mandible, the distal position of pore MXg and the presence of seta TR2, from Orectochilus Lacordaire, 1835 in the shape of the pretarsal setae PT1 and PT2, and from all other gyrinid genera with known larvae except Aulonogyrus Motschulsky, 1853 in the presence of a row of robust hook-like additional setae on the dorsointernal margin of the stipes.